PENAKSIRAN VOLUME POHON KOMERSIL MELALUI METODE PENARIKAN ACAK BERLAPIS (STRATIFIED RANDOM SAMPLING) BERDASARKAN KELAS LERENG DAN KERAPATAN TEGAKAN DI PT. LIMBANG GANECA - Gunawan Wibisono (ULIN: Jurnal Hutan Tropis, 2018)
This study aims to estimate the volume of commercial trees at PT. Limbang Ganeca based on Stratified Random Sampling carried out on the RKL VII area of the HPH with an area of 16,101 hectares with a forested area of 15,215 hectares. The area of the study area is 76.08 hectares which is divided into strata based on the slope class and stand density. Based on the results of stratification of topographic maps and vegetation maps, there is a combination of slope I class, slope II class, slope class III and three forest stratum with a combination of 9 forest strata. From this combination the diameter at breast height is measured to assess the volume of the tree.Based on the results of data analysis, slope class factors can be used in estimating volume, while stand density and interaction factors for these two factors cannot be used in estimating tree volume. From the results of measuring the diameter at breast height and calculating tree volume, the average volume of the area was 109,9898 m3 / hectare or around 108,309 to 111,487 m3 / hectare. While the overall volume of the RKL VII area ranges from 1,647,950,462 to 1,696,304,584 m3.